Identification and Validation of Reference Genes for Quantitative Real-Time PCR in Drosophila suzukii (Diptera: Drosophilidae) - Zhai, Yifan (Public Library of Science, 2014)
To accurately evaluate gene expression levels and obtain more accurate quantitative real-time RT-PCR (qRT-PCR) data, normalization relative to reliable reference gene(s) is required. Drosophila suzukii, is an invasive fruit pest native to East Asia, and recently invaded Europe and North America, the stability of its reference genes have not been previously investigated. In this study, ten candidate reference genes (RPL18, RPS3, AK, EF-1β, TBP, NADH, HSP22, GAPDH, Actin, α-Tubulin), were evaluated for their suitability as normalization genes under different biotic (developmental stage, tissue and population), and abiotic (photoperiod, temperature) conditions. The three statistical approaches (geNorm, NormFinder and BestKeeper) and one web-based comprehensive tool (RefFinder) were used to normalize analysis of the ten candidate reference genes identified α-Tubulin, TBP and AK as the most stable candidates, while HSP22 and Actin showed the lowest expression stability. We used three most stable genes (α-Tubulin, TBP and AK) and one unstably expressed gene to analyze the expression of P-glycoprotein in abamectin-resistant and sensitive strains, and the results were similar to reference genes α-Tubulin, TBP and AK, which show good stability, while the result of HSP22 has a certain bias. The three validated reference genes can be widely used for quantification of target gene expression with qRT-PCR technology in D.suzukii.